2021
DOI: 10.1155/2021/5583994
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Effect of Mesenchymal Stem Cells on T Cell Phenotypes in Autoimmune Diseases

Abstract: Research on mesenchymal stem cells (MSCs) starts from the earliest assumption that cells derived from the bone marrow have the ability to repair tissues. Several scientists have since documented the crucial role of bone marrow-derived MSCs (BM-MSCs) in processes such as embryonic bone and cartilage formation, adult fracture and tissue repair, and immunomodulatory activities in therapeutic applications. In addition to BM-MSCs, several sources of MSCs have been reported to possess tissue repair and immunoregulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 158 publications
0
4
0
Order By: Relevance
“…[52][53][54][55] costimulatory molecules associated with T cell activation. 56 UC-MSCs significantly reduce inflammation by extensively downregulating inflammatory products or cytotoxic mediators that act on immune cells and increase the level of the anti-inflammatory cytokine IL-10. 57 In addition to suppressing the immune response, UC-MSCs induce the production of IL-10-secreting regulatory T cells (Tregs) during local inflammation.…”
Section: Reduction In the Inflammatory Responsementioning
confidence: 99%
See 1 more Smart Citation
“…[52][53][54][55] costimulatory molecules associated with T cell activation. 56 UC-MSCs significantly reduce inflammation by extensively downregulating inflammatory products or cytotoxic mediators that act on immune cells and increase the level of the anti-inflammatory cytokine IL-10. 57 In addition to suppressing the immune response, UC-MSCs induce the production of IL-10-secreting regulatory T cells (Tregs) during local inflammation.…”
Section: Reduction In the Inflammatory Responsementioning
confidence: 99%
“…Our previous study was registered at ClinicalTrials.gov (NCT01547091), 8 been demonstrated for the clinical treatment of RA. Additionally, we conducted prospective phase I/II studies in 10 juvenile idiopathic arthritis (JIA) children 56 less than 17 years of age and 64 RA patients 7 aged 18 to 64 years. The patients were treated with a 40 mL of a UC-MSC suspension product (2 × 10 7 cells/20 mL) via intravenous injection.…”
Section: Clinical Researchmentioning
confidence: 99%
“…Previous studies have indicated that the CD39+ CD8+ Tregs subset played a crucial role in regulating immune homeostasis, preventing excessive immune responses, and controlling autoimmune diseases by producing inhibitory cytokines and regulatory receptors ( 47 , 49 ). Some studies have shown that SLE patients often have limited function or reduced numbers of Tregs ( 50 52 ). However, there is controversy regarding the quantity of Tregs in SLE research.…”
Section: Discussionmentioning
confidence: 99%
“…The results of studies have also indicated that MSCs can ameliorate the RA through different mechanisms such as suppression of Th17 cells, reduction of inflammatory cytokines, and up-regulation of Treg cells (Fig. 2 ) [ 44 ].
Fig.
…”
Section: Mesenchymal Stem Cellmentioning
confidence: 99%